The effect of an integrated neurofeedback and biofeedback training intervention on ice hockey shooting performance - Sommer, C.; Bertollo, M.; Werthner, P. (Journal of Sport & Exercise Psychology, 2020)
The purpose of this study was to investigate the effectiveness of a sensorimotor rhythm (SMR) neurofeedback training (NFT) and biofeedback training (BFT) intervention on ice hockey shooting performance. Specifically, the purpose was to examine (a) whether an NFT/BFT program could improve ice hockey shooting performance, (b) whether the implementation of an SMR-NFT intervention leads to neurological adaptations during performance, and (c) whether such neurological changes account for improvement in shooting performance. Using a longitudinal stratified random control design, results demonstrated that while both SMR-NFT/BFT and control groups improved performance, the rate of improvement for the SMR-NFT/BFT group was significantly higher than the control. Participants in the SMR-NFT/BFT group demonstrated the ability to significantly increase SMR power from pre- to postintervention in the lab. However, no significant changes in SMR power were found during shooting performance. This result may be suggestive of differing cortical activity present during motor-skill preparation.